PANDANGAN SOSIAL TERHADAP STRES DAN TRAUMA SETELAH BENCANA (Studi Kasus pada Masyarakat Aceh Pascabencana Gempa dan Tsunami Tahun 2004) - Andi Syahputra (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2012)
An individual or a communities that impact disaster will begin their new life, its mean to differ from condition likes before disaster was happened. This change is one of the condition which susceptible towards appearance many pressures in life to every human. Following the guidebook "self care-series Psycho-education" by Indonesia Red Cross cooperates with American Red Cross is mentioned that stress is condition which somebody have the body will react towards pressure/ difficultness/problems which it faced. And this reaction can be felted to each everybody. The painful’s event like natural’s disaster and/or armed conflict so more potential and risk full to get pressure/ stress and trauma in each people which were experienced. Stress can use much energy and also make somebody be weak because the bodies invulnerability system will descrease after experienced stress. The important of social support and religion character in return new spirit to life for Aceh’s society in continue the life has resqued many individual from stress or pressure which had experinced. Keyword: stress, trauma, social support, and religion character